Competitive Metal Coordination of Hexaaminotriphenylene on Cu(111) by Intrinsic Copper Versus Extrinsic Nickel Adatoms - Lischka, Matthias; Dong, Renhao; Wang, Mingchao; Martsinovich, Natalia; Fritton, Massimo; Grossmann, Lukas; Heckl, Wolfgang M.; Feng, Xinliang; Lackinger, Markus (Chemistry - A European Journal, 2019)
The interplay between the self-assembly and surface chemistry of 2,3,6,7,10,11-hexaaminotriphenylene (HATP) on Cu(111) was complementarily studied by high-resolution scanning tunneling microscopy (STM) and X-ray photoelectron spectroscopy (XPS) under ultra-high vacuum conditions. To shed light on the competitive metal coordination, comparative experiments were carried out on pristine and nickel-covered Cu(111). Directly after room-temperature deposition of HATP onto pristine Cu(111), self-assembled aggregates were observed by STM, and XPS results indicated still protonated amino groups. Annealing up to 200 °C activated the progressive single deprotonation of all amino groups as indicated by chemical shifts of both the N 1s and C 1s core levels in the XP spectra. This enabled the formation of topologically diverse π–d conjugated coordination networks with intrinsic copper adatoms. The basic motif of these networks was a metal–organic trimer, in which three HATP molecules were coordinated by Cu 3 clusters, as corroborated by the accompanying density functional theory (DFT) simulations. Additional deposition of more reactive nickel atoms resulted in both chemical and structural changes with deprotonation and formation of bis(diimino)–Ni bonded networks already at room temperature. Even though fused hexagonal metal-coordinated pores were observed, extended honeycomb networks remained elusive, as tentatively explained by the restricted reversibility of these metal–organic bonds.
CRIS-Team Scopus Importer:2022-04-14
Keywords: copper; metal–organic frameworks; scanning tunneling microscopy; self-assembly; surface chemistry